Discovery of a new class of triazole based inhibitors of acetyl transferase KAT2A - Roberta Pacifico; Nunzio Del Gaudio; Guglielmo Bove; Lucia Altucci; Lydia Siragusa; Gabriele Cruciani; Menotti Ruvo; Rosa Bellavita; Paolo Grieco; Mauro F. A. Adamo (Journal of Enzyme Inhibition and Medicinal Chemistry)
We have recently developed a new synthetic methodology that provided both N-aryl-5-hydroxytriazoles and N-pyridine-4-alkyl triazoles. A selection of these products was carried through virtual screening towards targets that are contemporary and validated for drug discovery and development. This study determined a number of potential structure target dyads of which N-pyridinium-4-carboxylic-5-alkyl triazole displayed the highest score specificity towards KAT2A. Binding affinity tests of abovementioned triazole and related analogs towards KAT2A confirmed the predictions of the in-silico assay. Finally, we have run in vitro inhibition assays of selected triazoles towards KAT2A; the ensemble of binding and inhibition assays delivered pyridyl-triazoles carboxylates as the prototype of a new class of inhibitors of KAT2A.